O-212 Applying sensors for assessment of occupational exposures in epidemiological studies: evaluation of sensors and preliminary findings. (14th March 2023) - Pronk, Anjoeka; Kuijpers, Eelco; Ruiter, Sander; Cauda, Emanuel; Warren, Nick; Bard, Delphine; Schlünssen, Vivi; Lund Würtz, Anne Mette; Cherrie, Mark; Loh, Miranda
Abstract : Introduction: Low cost sensors have potential for occupational exposure assessment by providing information on exposure profiles rather than time weighted averages (TWA). High resolution exposure data may advance our knowledge on how exposure patterns may affect (acute) health. We aimed to develop and deploy a multi-sensor box for assessing working life exposures (exposure at and outside work) during a working week in a case study on respiratory health as part of the EU Exposome Project for Health and Occupational Research (EPHOR) project. Material and Methods: A multi-exposure sensor box (particulate matter (PM), noise, light, UV and temperature) has been developed and is currently being deployed with the aim to assess exposures during a working week in relation to acute respiratory health among 300 mild asthma patients. The sensors were evaluated against conventional equipment separately. Several PM sensors were co-located in different occupational settings with gravimetric samplers and the Aerodynamic Particle Sizer (APS). Sensors for noise, light, UV and temperature were tested against conventional instruments in various environmental settings. Results and Conclusions: Low-cost PM sensors and the APS correlated reasonably well in different occupational settings (high-resolution data) (R2=0.4–0.6). Comparing the low-cost PM2.5 mass concentration from the sensors with the respirable gravimetric results (TWA) showed a moderate correlation (R2~0.5). A semi-quantitative comparison of TWA exposures with PM mass concentrations showed higher correlations (R2>0.75). A method for calibrating the PM sensor results to reflect different workplace and nonworkplace aerosols is being developed. The noise, light, UV and temperature sensors demonstrated R2 values of 0.9 and above with reference monitors in laboratory or field comparisons. Calibration equations have been developed based on these relationships. Along with the evaluation results of the different sensors, the preliminary results of the multi sensor box among ~25 case study subjects will be presented.